Are cytochrome P4502D6 and apolipoprotein E genotypes associated with long‐term cognitive and functional changes in patients treated with donepezil?. Issue 5 (1st April 2020) - Pamio, Maria V.; Trevisan, Caterina; Pigozzo, Sabrina; De Rui, Marina; Devita, Maria; Girardi, Agostino; Manzato, Enzo; Sergi, Giuseppe; Coin, Alessandra
Abstract : Aim: We investigated the associations of the single‐nucleotide polymorphism rs1080985 of cytochrome P4502D6 ( CYP2D6 ) and the apolipoprotein E ( APOE ) genotypes with cognitive and functional changes in patients treated with donepezil. Methods: Sixty‐five outpatients with Alzheimer's disease or mixed dementia being treated with donepezil were assessed at baseline and over 27 months. Changes in cognitive status, assessed with the Mini‐Mental State Examination, and in functional status, assessed by the Activities of Daily Living Scale and the Instrumental Activities of Daily Living Scale, were evaluated as a function of CYP2D6 and APOE genotypes by using linear mixed models. Multiplicative interactions between the CYP2D6 and APOE genotypes and time were investigated. Results: Individuals with the mutated CYP2D6 exhibited a slower decline in total Mini‐Mental State Examination scores, orientation, registration, and functional status than those with the wild type. A significant interaction between CYP2D6, APOE, and time was found for changes in the Activities of Daily Living Scale; among the ε4 carriers, those with the mutated CYP2D6 exhibited a slower decline on the Activities of Daily Living Scale than those with the wild type. Conclusion: The CYP2D6 and APOE genotypes may modulate the effectiveness of donepezil on cognitive and functional status.